2010
DOI: 10.1155/2010/537531
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Significance of HIF‐1α, CXCR4, and VEGF Expression in Colon Cancer

Abstract: We investigated the clinicopathologic significance of HIF-1, CXCR4, and VEGF expression using immumohistochemistry in human colon cancer. HIF-1, CXCR4, and VEGF high expression levels were correlated positively with TNM stage, lymph node involvement, and distant metastasis Furthermore, we found that combined high expression of any two of the three molecules (P = .028 for HIF-1/CXCR4, P = .007 for HIF-1/VEGF, and P = .004 for CXCR4/VEGF) had stronger correlation with lymph node metastasis than did each alone. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…I n a s t u d y e v a l u a t i n g V E G F a n d H I F -1 immunohistochemically in normal colon mucosa, both parameters were negative. In the same study, the overexpression rate was found to be 65% for VEGF and 44% for HIF-1α in tissues with colon cancer (Wu et al, 2010). In this study, the rate of high VEGF expression was found to be 57% and overexpression of HIF-1α to be 55% in tissues with metastatic colorectal cancer.…”
Section: Discussionsupporting
confidence: 66%
“…I n a s t u d y e v a l u a t i n g V E G F a n d H I F -1 immunohistochemically in normal colon mucosa, both parameters were negative. In the same study, the overexpression rate was found to be 65% for VEGF and 44% for HIF-1α in tissues with colon cancer (Wu et al, 2010). In this study, the rate of high VEGF expression was found to be 57% and overexpression of HIF-1α to be 55% in tissues with metastatic colorectal cancer.…”
Section: Discussionsupporting
confidence: 66%
“…Hypoxic conditions allow HIF-1α to bind to HIF-1β and then become an active transcriptional factor, while the presence of oxygen leads to the degradation of HIF-1α. In a previous study, the immunohistochemical analysis in 68 CRC patients has shown that high expression levels of HIF-1α is positively associated with TNM stage, lymph node involvement, and distant metastasis (Wu et al, 2010). Similarly, another study has shown that HIF-1α over-expression is associated with the poor prognosis in a cohort of 731 CRC patients (Baba et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Among the 18 articles, six of those were excluded due to laboratory studies, non-original articles (review), or studies irrelevant to the current analysis. Eventually, the remaining twelve studies were included for further analysis (Joseph et al, 2005;Alessandro et al, 2006;Fukunaga et al, 2006;N Yoshitake et al, 2008;Frank et al, 2009;Shang et al, 2010;Yugang et al, 2010;Adam et al, 2012;Crescenzo et al, 2013;Tinghua et al, 2013;Ying et al, 2014;Shinichiro et al, 2014) (Figure 1). …”
Section: Identification Of Relevant Studiesmentioning
confidence: 99%